ANALISA INDEKS BIAYA UNTUK PEKERJAAN BETON BERTULANG DENGAN MENGGUNAKAN METODE SNI 7394-2008 DAN LAPANGAN (Studi Kasus pada Proyek Pembangunan Asrama STIKES CHMK Tahap III) - Messah, Yunita A.; Sina, Dantje A. T.; Manubulu, Christiani C. (Jurnal Teknik Sipil, 2013)
The index cost affect the amount of unit price construction work. Cost index used in the calculation analysis of unit price refers to the Standar Nasional Indonesia (SNI). SNI describe about the average labor productivity in Indonesia. Labor productivity are different depend on work experience, cultural origins, and the others. This study was conducted to know the costs index of labor in Kupang by took one of case study on STIKES CHMK Dormitory Construction Project in third Phased. Cost index of reinforced concrete in this project, obtained by doingreal observation for the total of labor and time required to complete each item of reinforced concrete, especially the workfrom column,beam and plate and it began from the work of iron, formwork, casting up to demolition formwork.Then the observationsresult were analyzed descriptively. Based on the analysis result, the amount of the cost index is 0.0208 foreman: 0.0377 the head of handyman: 0.09929 handyman: 0.2502 worker to install 1m2 formwork, 0.0044 foreman: 0.0177 the head of handyman: 0.0268 handyman : 0.0796 worker to work 10 kg iron, and 0.0340 foreman: 0.0272 the head of handyman: 0.1427 handyman: 1.1888 worker to make 1m3concrete. This index used in the analysis of the differentation of labor presentage based on SNI and field method and continued with the calculation of unit price for each work item which used SNI and field method.